Hemi-Slant Submanifold of (LCS)n-Manifold - Payel Karmakar; Arindam Bhattacharyya (Journal of the Indonesian Mathematical Society, 2022)
In this paper we analyse briefly some properties of hemi-slant sub-manifold of (LCS)n-manifold. Here we discuss about some necessary and sufficient conditions for distributions to be integrable and obtain some results in this direction. We also study the geometry of leaves of hemi-slant submanifold of (LCS)n-manifold. At last we give an example of a hemi-slant submanifold of an (LCS)n-manifold.